(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study investigates the physicochemical properties of vegetable oil-based lubricants derived from sesame and groundnut oils, with emphasis on the effect of a composite chemical additive. The additive formulation consisted of a fine mixture of aluminum oxide (Al₂O₃) and magnesium sulfate heptahydrate (MgSO₄·7H₂O) combined with hydrogen peroxide and oleum, applied at varying concentration levels (10%, 20%, 30%, 40%, and 50% by volume). Key properties evaluated include kinematic viscosity, pour point, flash point, cloud point, specific gravity, thermal conductivity, acid value, free fatty acid, and saponification value, following established ASTM standards. Results indicate that increasing the additive concentration enhances the thermal conductivity of both oils, with sesame oil demonstrating superior thermal performance compared to groundnut oil. Conversely, groundnut oil exhibits better viscosity characteristics at higher additive concentrations, retaining greater lubricity, whereas sesame oil’s viscosity decreases with increasing additive levels. Both oils, however, exhibit declining thermal conductivity and lubricity at elevated temperatures (50–70°C), revealing a significant limitation for high-temperature industrial applications. Physicochemical analysis further confirms that groundnut oil has a higher flash point (265°C) and saponification value, while sesame oil presents a lower pour point (−14.67°C), indicating better cold-temperature performance. These findings suggest that optimizing composite additive formulations can significantly improve the performance of bio-lubricants; nonetheless, further research is required to address high-temperature stability before these lubricants can be adopted for broader industrial use.